GAAROT: AN INDIGENOUS DRIVE-IN FISHING GEAR TO CAPTURE LOACHES IN NAGPUR DISTRICT, MAHARASHTRA - Ghatge, Swapnil S.; Shelke, Shamkant T.; Belsare, Sachin W.; Gore, Sandeep B. (Journal of Indian Fisheries Association, 2014)
Riverine habitat is rich in fish biodiversity and many traditional fishing operations are practiced in river. Fish is an integral part of food habit of villages in majority of fishing villages of India. The livelihood of inland fishermen community in villages in mainly dependent on fishing of local fish species. Successful fishing operation largely depends upon the comprehensive understanding of fish biology, habitat of the fish, selection of appropriate fishing methods and correctly designed fishing gear. Many traditional fishing gears are used for fishing in inland water bodies of which only some are documented while many need to be documented. This paper is an attempt to document the traditional inland fishing gear, gaarot: a type of drive in fishing gear used to capture loaches of family Nemacheilidae which is operated by fishermen community â€œBhoiâ€ in the Madar river of Nagpur District.Â Key words: Traditional fishing practices, community fishing, drive-in fishing, gaarot, loaches, Maharashtra. Â